Influence of M23C6 carbides on the heterogeneous strain development in annealed 420 stainless steel. (November 2020) - Hidalgo, J.; Vittorietti, M.; Farahani, H.; Vercruysse, F.; Petrov, R.; Sietsma, J.
Abstract: Understanding the local strain enhancement and lattice distortion resulting from different microstructure features in metal alloys is crucial in many engineering processes. The development of heterogeneous strain not only plays an important role in the work hardening of the material but also in other processes such as recrystallization and damage inheritance and fracture. Isolating the contribution of precipitates to the development of heterogeneous strain can be challenging due to the presence of grain boundaries or other microstructure features that might cause ambiguous interpretation. In this work a statistical analysis of local strains measured by electron back scatter diffraction and crystal plasticity based simulations are combined to determine the effect of M23 C6 carbides on the deformation of an annealed AISI 420 steel. Results suggest that carbides provide a more effective hardening at low plastic strain by a predominant long-range interaction mechanism than that of a pure ferritic microstructure. Carbides not only influence local strain directly by elastic incompatibilities with the ferritic matrix, but also the spatial interactions between ferrite grains. Carbides placed at the grain boundaries enhanced the development of strain near ferrite grain boundaries. However the positive effect of carbides and grain boundaries to develop high local strains is mitigated at regions with high density of carbides and ferrite grain boundaries. Graphical abstract: Image, graphical abstract